SME alliance motives and knowledge modes - Johansson, Johan; Ylinenpää, Håkan (Luleå tekniska universitet, Innovation och Design, 2007)
Strategic alliances are an emergent organization form that is increasingly gaining interest over go-it-alone strategies for organizations to achieve fast and economical growth. Drawing upon the resource based view of the firm several previous studies have viewed alliances as a quest for resources. One important objective identified in strategic alliances is the sharing of knowledge such as technology, advanced skills and organizational capability. Most of the strategic alliance literature however focuses on large-firm alliances, implicating that smaller firms with a more limited pool of in-house resources and a more obvious need to access resources beyond the limits of their own organisation often have been neglected. In this paper we study how SMEs focus on different kind of knowledge modes together with partners in a strategic alliance.For this purpose a case study approach has been employed to investigate and analyse the case of EVONET Industrial Partners, a strategic alliance consisting of six manufacturing companies in Northern Sweden aiming for a stronger position as suppliers to car and heavy truck industry. The alliance has been studied over three years, and data has been continuously collected through 63 interviews, participating observations and from secondary sources. The empirical results show that accessing (rather than acquiring) knowledge has been a central interest for the alliance firms. The empirical results also indicate the importance of concrete and applied projects that are jointly carried through, since joint projects foster personal networks and trust between employees in the participating firms enabling exchange of, primarily, knowledge based on know-how and know-who. On a more theoretical level, the study contributes with addressing the link between different strategic orientations of partnerships and the kinds of knowledge and knowledge exchange/transfer that becomes critical in different strategic alliances. Different types of strategic alliances may be expected to exploit different ...